Evaluation of the level of 5'-nucleotidase and some biochemical parameters in the sera of beta-thalassemia patients - Sameer M. Al-Gorany; Mohammed Rajeh Altutnchi (Tikrit Journal of Pure Science, 2023)
One of the hydrolytic enzymes that catalyzes the hydrolysis of 5' -nucleotides into ribonucleosides and phosphate is the 5'nucleotidase, which is found in several organs. Oxidative stress shows depletion of antioxidants, such as glutathione (GSH), and the increased concentration of product of lipid peroxidation, such as MDA. The study comprised a total of 54 subjects including patients with beta thalassemia (n=27) and healthy volunteers (n=27) matched by age and gender. Hematology (Hb and % PCV), 5'-nucleotidase, Ferritin, GSH and MDA were measured using different methods and devices. The 5'nucleotidase, Ferritin, and MDA levels were significantly increased (p<0.001) in beta-thalassemia patients compared to the controls. As opposed to that, the Hb, % PCV and GSH levels were significantly decreased (p<0.001) in patients with beta-thalassemia. There was a negative significant correlation (r = -0.146, -0.245, p<0.05) between Hb and 5'- NT enzyme and PCV% with 5'- NT enzyme, respectively. While Hb had a high significant correlation (r = 0.956, p<0.05) with PCV%. In addition, 5'- NT enzyme had a positive significant correlation with GSH, MDA and Ferritin (r = 0.584, 0.442, 0.735, p<0.05), respectively. The present findings indicated an increase in the level of effectiveness of the 5'nucleotidase enzyme, ferritin and GSH in β thalassemia patients while decreasing in MDA.